Progression and regression of keratoconus in an Iranian population - Alireza Jamali; Hassan Hashemi; Payam Nabovati; Mehdi Khabazkhoob (Scientific Reports)
Abstract To evaluate temporal changes in keratoconus (KCN) in individuals of different ages. In this historical cohort study, participants diagnosed with KCN underwent two evaluations at separate time points. Each evaluation included corneal imaging using Pentacam-HR, ocular examinations, subjective refraction, and visual acuity assessments. KCN changes were defined as a minimum 1.00 D change in the anterior maximum keratometry (kmax), categorizing participants as regressive, stable, or progressive. A total of 838 participants (mean age 30.90 ± 8.30 years; 62.5% male) were assessed twice over an average follow-up period of 74.38 ± 42.21 months. Regression occurred in 81 eyes (mean Kmax change: -2.05 ± 1.27 D), progression in 196 eyes (mean Kmax change: +4.03 ± 4.58 D), and stability in 561 eyes (mean Kmax change: +0.07 ± 0.43 D); Cases of both progression and regression were observed across all 10-year age groups. At baseline, the regressive group had the highest corneal steepening, while the stable group had the least steepening (p < 0.05). The spherical equivalent was more negative in all three groups in the second examination except for those with ages more than 50 years (p < 0.05). Associations were observed between Kmax changes and male sex (β=-0.58; p = 0.013), posterior flat keratometry (β = 0.75; p < 0.001), posterior peripheral curvature (β=-1.91; p < 0.001), index of surface variance (β = 0.03; p < 0.001), keratoconus index (β = 4.04; p = 0.012), and minimum curvature (β = 1.05; p = 0.003). This study highlights that KCN can progress or regress at any age, challenging the traditional belief that it stabilizes in adulthood. The findings highlight the necessity of regular monitoring and individualized management strategies, particularly in cases where structural or visual changes may impact clinical decisions.